2010
DOI: 10.1123/jab.26.3.324
|View full text |Cite
|
Sign up to set email alerts
|

Determination of the Drag Coefficient during the First and Second Gliding Positions of the Breaststroke Underwater Stroke

Abstract: The purpose of the current study was to assess and to compare the hydrodynamics of the first and second gliding positions of the breaststroke underwater stroke used after starts and turns, considering drag force (D), drag coefficient (CD) and cross-sectional area (S). Twelve national-level swimmers were tested (6 males and 6 females, respectively 18.2 ± 4.0 and 17.3 ± 3.0 years old). Hydrodynamic parameters were assessed through inverse dynamics from the velocity to time curve characteristic of the underwater … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
55
2
5

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 54 publications
(66 citation statements)
references
References 12 publications
4
55
2
5
Order By: Relevance
“…Between these glides the swimmer performs an underwater arms' stroke. Studies reported differences in the passive drag gliding in the two different positions noted earlier (Marinho et al, 2009;Vilas-Boas et al, 2010). Because the Breaststroke start is restricted to one single underwater stroke, swimmers do try to optimise their underwater distance breakout by decreasing the passive drag (Marinho et al, 2009;Naemi, Easson, & Sanders, 2010;Vilas-Boas et al, 2010) and/or enhancing the water entry (Tor et al, 2015).…”
Section: Starting Performancementioning
confidence: 99%
See 1 more Smart Citation
“…Between these glides the swimmer performs an underwater arms' stroke. Studies reported differences in the passive drag gliding in the two different positions noted earlier (Marinho et al, 2009;Vilas-Boas et al, 2010). Because the Breaststroke start is restricted to one single underwater stroke, swimmers do try to optimise their underwater distance breakout by decreasing the passive drag (Marinho et al, 2009;Naemi, Easson, & Sanders, 2010;Vilas-Boas et al, 2010) and/or enhancing the water entry (Tor et al, 2015).…”
Section: Starting Performancementioning
confidence: 99%
“…Regarding Breaststroke, this is the swim stroke where swimmers (males and females) are slower at the 15-m out and show the shortest underwater breakout distance (except Freestyle in both sexes). Because of the rules constraints, swimmers are advised to adopt the most streamlined position as they can in this first gliding position (i.e., arms extended at the front) (Marinho, Barbosa, Rouboa, & Silva, 2011;Vilas-Boas et al, 2010).…”
Section: Turning Performancementioning
confidence: 99%
“…In competitive swimming (i) the resultant force is the balance between propulsion and drag; (ii) the inertial term includes the swimmer's body mass plus the added water mass, and (iii) the body's acceleration (Seifert, Toussaint, Alberty, Schnitzler, & Chollet, 2010;Vilas-Boas et al, 2010):…”
Section: Introductionmentioning
confidence: 99%
“…We were very pleased to observe similar results obtained through CFD and through inverse dynamics. Regarding drag coefficient, Vilas-Boas et al (2009) reported that the position with the arms at the front (position adopted during the first gliding) presented about 65 % of the drag coefficient values of the position with the arms aside the trunk (position adopted during the second gliding). Another interesting research concerning the underwater gliding and the most advantageous postures to improve performance was conducted by Marinho et al (2009c).…”
Section: Minimizing Drag After Start and Turnsmentioning
confidence: 99%
“…For the breaststroke underwater phase after start and turns, it was concluded that the first glide, performed with the arms at the front, must be emphasized in relation to the second glide, performed with the arms along the trunk. Vilas-Boas et al (2009) attempted to analyse the same situations but through inverse dynamics. This procedure was based on the experimental velocity to time gliding curve and the swimmers' inertia performed during the first and second gliding positions of the breaststroke underwater stroke.…”
Section: Minimizing Drag After Start and Turnsmentioning
confidence: 99%